Implmentasi TQM dalam Perguruan Tinggi: Sebuah emikiran Pembaruan Pendidikan - Rosita EK (Fakultas Ilmu Pendidikan UNY, 2003)
Implmentasi TQM dalam Perguruan Tinggi: Sebuah emikiran Pembaruan Pendidikan